1985
DOI: 10.2170/jjphysiol.35.321
|View full text |Cite
|
Sign up to set email alerts
|

Non-uniform effects of neurohumoral agents on the internal diameter in parallel and series arranged small arteries in rabbit hindlimb.

Abstract: Using X-ray angiography, the internal diameter (ID) of 31 sites of arteries in the hindlimb, i.e., the iliac, main femoral, profundal femoral, circumflex femoral, saphenous, and popliteal arteries, was measured in anesthetized rabbits. ID under the control condition was 294-1,796 µm, but was changed to 376-1,828 µm, 127-1,914 µm, and 423-2,098 ,um with administration of hexamethonium bromide, noradrenaline, and phentolamine, respectively. The constrictor effects of noradrenaline and plasma catecholamine were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The contractile synergy between femoral EP 3 receptors and a 1 ARs described here and by others (Hung et al, 2006) may contribute to the well documented peripheral muscle pain (myalgia) reported in patients with PAH receiving treatment with PGI 2 analogs (Tapson et al, 2012(Tapson et al, , 2013Pagani-Estévez et al, 2017). Involvement of other lower limb arteries that are under adrenergic control (e.g., the popliteal artery) (Sada et al, 1985) cannot be excluded. Although the development of pain is considered to arise from IP and EP 3 receptor-dependent sensitization of sensory afferent neurons (Nakae et al, 2005;Southall and Vasko, 2001), our data support an additional vascular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The contractile synergy between femoral EP 3 receptors and a 1 ARs described here and by others (Hung et al, 2006) may contribute to the well documented peripheral muscle pain (myalgia) reported in patients with PAH receiving treatment with PGI 2 analogs (Tapson et al, 2012(Tapson et al, , 2013Pagani-Estévez et al, 2017). Involvement of other lower limb arteries that are under adrenergic control (e.g., the popliteal artery) (Sada et al, 1985) cannot be excluded. Although the development of pain is considered to arise from IP and EP 3 receptor-dependent sensitization of sensory afferent neurons (Nakae et al, 2005;Southall and Vasko, 2001), our data support an additional vascular mechanism.…”
Section: Discussionmentioning
confidence: 99%